2017
DOI: 10.1158/1535-7163.mct-17-0060
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine Priming Enhances Mucin 1 Inhibition Mediated Disruption of Redox Homeostasis in Cutaneous T-Cell Lymphoma

Abstract: Cutaneous T-cell lymphoma (CTCL) is a heterogeneous neoplasm and patients with relapsed/refractory disease exhibit resistance to standard therapies. We have previously demonstrated that the MUC1-C oncoprotein plays a critical role in protection from oxidative stress in CTCL cells. Targeting of MUC1-C with a pharmacologic inhibitor, GO-203, was associated with apoptosis in CTCL. However, disease responses were incomplete underscoring the need for combinatorial strategies that could exploit the vulnerability of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Treatment with a combination of DAC and temozolomide (TMZ) has also produced similar synergistic results in vitro and in vivo, resulting in complete response in TMZ-resistant diffuse large B-cell lymphoma murine xenograft models (20). Additionally, a xenograft murine model of CTCL showed that DAC and Mucin-1 C-terminal subunit inhibition (GO-203) resulted in a significant reduction in tumor volume compared to either agent alone (10). A phase I study found that DAC resulted in better treatment activation and safety in patients with advanced solid tumors and non-Hodgkin's lymphomas (21).…”
Section: Discussionmentioning
confidence: 96%
“…Treatment with a combination of DAC and temozolomide (TMZ) has also produced similar synergistic results in vitro and in vivo, resulting in complete response in TMZ-resistant diffuse large B-cell lymphoma murine xenograft models (20). Additionally, a xenograft murine model of CTCL showed that DAC and Mucin-1 C-terminal subunit inhibition (GO-203) resulted in a significant reduction in tumor volume compared to either agent alone (10). A phase I study found that DAC resulted in better treatment activation and safety in patients with advanced solid tumors and non-Hodgkin's lymphomas (21).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, due to patients' individualities and tumors heterogeneity, variable response rates are often observed making the identification of more effective drugs very urgent [272,273]. In this regard, the concomitant inhibition of antioxidant circuits and metabolic pathways that support the redox balance of malignant cells, delineates a promising anti-cancer strategy [274][275][276][277][278][279][280][281][282][283]. It is known that most of the metabolic changes promoting cancer cells proliferation and tumor growth induce also an increased ROS generation, counterbalanced by an antioxidant response that prevents cell death [234,284,285].…”
Section: Strategies To Negatively Modulate Nrf2 Signaling/pathwaymentioning
confidence: 99%
“…It is induced already at 2 h in response to indirubin treatment and resides upstream of the downregulation of XIAP and c-FLIP as well as upstream of the loss of MMP, suggesting a signaling cascade as shown in Figure 6c. Also for other treatments in CTCL cells, relations of ROS and apoptosis induction have been reported, such as for an inhibitor of the antioxidative protein mucin 1 [37], for silencing of the enhancer of zeste homolog 2 (EZH2) [38] and for doxycycline [39]. Thus, ROS production appears to be an important cellular signaling step related to the induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%